METHODS OF ORGANIZATION IN FINE ARTS LESSONS BASED ON MODERN PEDAGOGICAL TECHNOLOGIES - Turayev Olimjon Suvanovich (American Journals, 2024)
In this article, the skills and methods of using modern pedagogical technologies in the process of conducting fine art lessons, the application of pedagogical renewal processes to educational practice, and the issue of pedagogical technology in teaching fine arts at school are fully described.
Keywords: fine art, painting, pedagogical technologies, renewal, thematic composition.